Application of The Family Support Model to Increase Elderly Independence - Tri Prabowo; Bondan Palestin; Atik Badi'ah; Muhammad Najib (JURNAL INFO KESEHATAN, 2025)
Elderly independence is essential for maintaining quality of life and functional ability. Family involvement has been shown to support this independence, but evidence from quasi-experimental studies in Indonesia remains limited. This study aimed to evaluate the effect of the Family Support Model on elderly independence in selected Public Health Center areas of Yogyakarta and Central Java. A quasi-experimental design with pre-post-test control group was conducted from March to October 2022. A total of 96 elderly participants without chronic illness were purposively assigned to experimental (n=48) and control groups (n=48). The intervention applied the Family Support Model, which included family education, structured assistance with daily activities, weekly follow-ups, and joint problem-solving involving families and health personnel. Independence was assessed using a validated questionnaire based on the Katz Index, covering both Basic (BADL) and Instrumental Activities of Daily Living (IADL). Measurements were conducted at baseline, and at one, two, and three months post-intervention. Results showed a significant increase in self-care independence in the experimental group from 0% to 97.8%, and a decrease in self-care deficit from 63% to 2.2%. In contrast, the control group showed modest improvements, with independence increasing from 0% to 32.6%, and deficit decreasing from 78.3% to 67.4%. Repeated measures ANOVA revealed significant differences between groups over time (p < 0.001). The conclusion is the Family Support Model is effective in enhancing elderly independence. It can be adopted as a practical, community-based intervention to sustain daily functioning and improve the quality of life among older adults.